2019
DOI: 10.32744/pse.2019.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of social and cultural adaptation of foreign students in Russian universities

Abstract: Барьеры социокультурной адаптации иностранных студентов в российских вузахДанная статья представляет результаты исследования материалов организованного на сайте Министерства образования Новосибирской области онлайнанкетирования иностранных студентов, обучающихся в вузах г. Новосибирска. Цель исследования -выявить барьеры социокультурной адаптации иностранных студентов в России. Основной методологический подход к решению поставленных задач междисциплинарный, находящийся на стыке наук, позволяющий интегрировать … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Language is the basic mechanism of human communication [40]. It should be mentioned that language barrier is a major problem in attracting foreign students to study in Russian regional universities [41][42][43]. The respondents indicated difficulties in both understanding university professors and interacting with the representatives of the host community on a daily basis (sellers, busmen, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Language is the basic mechanism of human communication [40]. It should be mentioned that language barrier is a major problem in attracting foreign students to study in Russian regional universities [41][42][43]. The respondents indicated difficulties in both understanding university professors and interacting with the representatives of the host community on a daily basis (sellers, busmen, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Works of Antipiev (2009), Akhtarieva, Ibragimova, and Puchinina (2019), Beregovaya, Lopatina, and Oturgasheva (2019), and Koslovtseva and Tolstova (2019) are devoted to some aspects of the adaptation of Foreign Students. Kamalov's (2015) scientists, Chubko et al (2019), Meng, Zhu, and Cao (2018), Kim, Kim, and Kim (2019), Zhou, Zhao, and Dawson (2020), and Santillan et al (2018) write about a technique of language adaptation of foreign students and practice of training in Russian the foreign students.…”
Section: Condition Of Readiness Of a Problemmentioning
confidence: 99%
“…Authors Beregovaya, Lopatina, and Oturgasheva (2019) exploring barriers to sociocultural adaptation of foreign students, concluded that the main barrier to successful sociocultural adaptation of foreign students is the language barrier, which significantly affects overcoming other barriers -cross-cultural and academic. Kozlovtseva and Tolstova (2019) explores the formation of the image of the Russian world as an aspect of the sociocultural adaptation of foreigners in the process of teaching Russian.…”
Section: Review Of Russian Academic Literaturementioning
confidence: 99%
“…По мере роста глобальной политической напряжённости, вызывающей опасения у иностранных студентов в отношении толерантного к ним отношения со стороны местного населения, в вузах востребованы специальные мероприятия, направленные на создание комфортной среды пребывания. Проведённое ранее исследование авторов статьи по выявлению барьеров социокультурной адаптации иностранных студентов в российских вузах [1] показало, что быстрое или медленное протекание данного процесса отражается на качестве жизни и академических успехах иностранных учащихся, а также зависит от того, как и с помощью чего преодолеваются трудности.…”
Section: постановка проблемы цели исследованияunclassified
“…чел. 1 За последние десятилетия возросла конкуренция вузов за привлечение иностранных студентов благодаря созданию для них благоприятной среды для обучения и проживания в принимающей стране.…”
Section: Introductionunclassified